R-CHOP-Associated Graves’ Hyperthyroidism - Natalie Mora; Katherine N. Vu; Thanh D. Hoang; Vinh Q. Mai; Mohamed K.M. Shakir (Case Reports in Oncology, 2019)
Radiation-induced thyroid dysfunction following oncologic treatment is not uncommon, however limited literature data has been found on patients that underwent chemotherapy only. A change in thyrometabolic autoimmune status is also a rare entity. We present a case of newly diagnosed Graves’ thyrotoxicosis following a successful R-CHOP (Rituximab, Cyclophosphamide, Doxorubicine, Vincristine and Prednisone) treatment in a patient with concurrent abdominal and thyroid diffuse large B-cell lymphoma (DLBCL). Following chemotherapy, PET CT showed resolution of FDG-avid thyroid nodule as well as no evidence of the thyroid mass on repeat ultrasound. Her thyroid function also normalized. During her follow-up visit, patient reported significant unintentional weight loss and persistent fatigue over the past couple months. Repeat laboratory evaluation revealed TSH 0.005 mIU/mL, FT4 6.73 ng/dL and thyroid stimulating immunoglobulin (TSI) 535 (ref <140%). She was started on methimazole followed by radioactive iodine therapy. This unique case of Graves’ disease following R-CHOP treatment in patients with known Hashimoto’s and thyroid lymphoma is one of the first to be reported in the literature. The swing of pendulum from Hashimoto’s to Graves’ disease is very uncommon. As clinicians, we need to continue monitoring for clinical and biochemical thyroid dysfunction in this subset of population.